Electrophysiological remodeling in primary versus secondary cardiac hypertrophy: a study in human cardiomyocytes. (10th June 2022) - Palandri, C; Santini, L; Giammarino, L; Musumeci, M; Olivotto, I; Cerbai, E; Coppini, R
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministero dell'università e della ricerca Electrophysiological remodeling in primary versus secondary cardiac hypertrophy: a study in human cardiomyocytes Introduction: Myocardial hypertrophy is an adaptive condition to hemodynamic stress, characterized by the increase in size of the cardiomyocytes and in the cardiac mass. It involves more frequently the left ventricle (LV) and leads to an enhanced risk of arrhythmias; it's characterized by the increase walls thickness and by a large remodelling of the cardiac tissue in terms of fibrosis, impaired calcium handling and ion current balance. The LV hypertrophy could be induced by genetic abnormalities, such as in hypertrophic cardiomyopathy (HCM) or it could be secondary to other pathological conditions, like aortic stenosis (SAO-HT). Purpose: In this work we will compare the mechanisms that mainly determine primitive (HCM samples) or secondary (to aortic stenosis: SAO-HT) LV hypertrophy to assess common points and disagreements. Methods: Human septal specimens from HCM, SAO-HT and control (CTRL) surgical patients were collected, tissue was in part rapidly frozen, in part processed to isolate responsive single cells or trabeculae. We performed patch clamp experiments to measured action potential duration (APD) and calcium current (ICaL). To study the Ca2+ handling we performed imaging analysis; isolated cardiomyocytes were loaded with a Ca2+ sensitive dye (CAL530) by incubating cells for 30 min, then we evaluate the calcium transients at different stimulation frequencies. Results: We evaluated APD, ICaL, and Ca2+ handling in the 3 groups: HCM, SAO-HT and CTRL cardiomyocytes. Both pathological groups show to be depolarized, to have a prolonged APD, diastolic Ca2+ concentration is higher and the kinetics are slower than in CTRL cardiomyocytes. HCM cardiomyocytes has longer APD than SAO-HT and higher diastolic Ca2+ concentration, HCM also shows longer kinetics of the decay phase of the Ca2+ transient compare to SAO-HT. The ICaL is comparable between CTRL and SAO-HT, it is higher in HCM and the inactivation kinetics are slower. Discussion and Conclusion: We evaluate the electrophysiological differences among cardiomyocytes derived from a secondary or primary myocardial hypertrophy and from non-hypertrophic myocardia. Alterations in the two groups of pathological samples are similar. Both shows slowed Ca2+ transient kinetics, that slow down the relaxation machinery, and increase diastolic Ca2+ concentration, that could cause arrhythmic events (DAD). The increase in diastolic Ca2+ could also be responsible for the hyperactivation of the CAMK-II that has among its target ICaL channel and the Na2+ channel that are hyperactivated causing the prolongation of APD. The functional alterations observed in the hypertrophic cardiomyocytes could be considered not as disease specific response but a mechanism of adaptation to the hypertrophy and to diastolic dysfunction, those are more serious where the hypertrophy is genetic determined.